A dynamic‐efficiency rationale for public investment in the health of the young. (August 2014) - Andersen, Torben M.; Bhattacharya, Joydeep
Abstract In this paper we assume away standard distributional and static‐efficiency arguments for public health and instead seek a dynamic efficiency rationale. We study a lifecycle model wherein young agents make health investments to reduce mortality risk. We identify a welfare rationale for public health under dynamic efficiency and exogenous mortality even when private and public investments are perfect substitutes. If health investment reduces mortality risk but individuals do not internalize its effect on the life‐annuity interest rate, the "Philipson‐Becker effect" emerges; when the young are net borrowers, this works together with dynamic efficiency to support a role for public health.